Athletes' imagery use from a team-level perspective and team cohesion. Issue 4 (1st October 2016) - Curtin, Kimberley D.; Munroe-Chandler, Krista J.; Loughead, Todd M.
Abstract : While a positive relationship has been established between imagery and team-level constructs (e.g. collective-efficacy and cohesion), those studies have examined imagery from an individual-level perspective (e.g. "I imagine myself being mentally tough"). Therefore, the purpose of the current study was to explore the relationship of athlete imagery use from a team-level perspective to team cohesion. Interdependent sport team athletes ( N  = 284) completed the Group Environment Questionnaire in order to measure team cohesion, and the Sport Imagery Questionnaire-Team Sport which was modified from the original Sport Imagery Questionnaire to assess the frequency of athlete's imagery use from a team-level perspective. Multiple regression analysis revealed that motivation general-mastery imagery was significantly related to the cohesion dimensions of group integration-task (21%), individual attractions to the group-task (11%), and individual attractions to the group-social (13%). Findings suggest that motivational imagery from a team-level perspective should be emphasised on sport teams in order to increase team cohesion.